A Dream that Remains a Dream: The Case of 'Sultana’s Dream' by Begum Rokeya - Asha, Monwara Khatun (Technium Social Sciences Journal, 2021)
For the proper progression of any nation, it is undeniable that women who occupy more or less half of the total population should be considered effective resources. However, even in this 21st century, the reality goes contradictory to it. That is, the dream of a world, where women can enjoy their basic human rights and can proclaim themselves as the human being rather than being considered as only mere women, is still a dream. This paper deals with the writing of Begum Rokeya Shakhawat Hossain’s ‘Sultana’s Dream’ and aims to analyze this text to make a comparative study between the utopian world portrayed in ‘Sultana’s Dream’ and our real world in order to show the unchanged status of women even today. This research is based on qualitative method. I think this research will add a new dimension to the existing field of feminism and is beneficiary for the people who are conscious of the rights of women and in support of building an egalitarian world.